Sonic Hedgehog regulates thymic epithelial cell differentiation. (April 2016) - Saldaña, José Ignacio; Solanki, Anisha; Lau, Ching-In; Sahni, Hemant; Ross, Susan; Furmanski, Anna L.; Ono, Masahiro; Holländer, Georg; Crompton, Tessa
Abstract: Sonic Hedgehog (Shh) is expressed in the thymus, where it regulates T cell development. Here we investigated the influence of Shh on thymic epithelial cell (TEC) development. Components of the Hedgehog (Hh) signalling pathway were expressed by TEC, and use of a Gli Binding Site-green fluorescence protein (GFP) transgenic reporter mouse demonstrated active Hh-dependent transcription in TEC in the foetal and adult thymus. Analysis of Shh-deficient foetal thymus organ cultures (FTOC) showed that Shh is required for normal TEC differentiation. Shh-deficient foetal thymus contained fewer TEC than wild type (WT), the proportion of medullary TEC was reduced relative to cortical TEC, and cell surface expression of MHC Class II molecules was increased on both cortical and medullary TEC populations. In contrast, the Gli3-deficient thymus, which shows increased Hh-dependent transcription in thymic stroma, had increased numbers of TEC, but decreased cell surface expression of MHC Class II molecules on both cortical and medullary TEC. Neutralisation of endogenous Hh proteins in WT FTOC led to a reduction in TEC numbers, and in the proportion of mature Aire-expressing medullary TEC, but an increase in cell surface expression of MHC Class II molecules on medullary TEC. Likewise, conditional deletion of Shh from TEC in the adult thymus resulted in alterations in TEC differentiation and consequent changes in T cell development. TEC numbers, and the proportion of mature Aire-expressing medullary TEC were reduced, and cell surface expression of MHC Class II molecules on medullary TEC was increased. Differentiation of mature CD4 and CD8 single positive thymocytes was increased, demonstrating the regulatory role of Shh production by TEC on T cell development. Treatment of human thymus explants with recombinant Shh or neutralising anti-Shh antibody indicated that the Hedgehog pathway is also involved in regulation of differentiation from DP to mature SP T cells in the human thymus. Highlights: TEC express components of the Hedgehog signalling pathway and transduce it's signals. Sonic hedgehog (Shh) is required for normal TEC development. Sonic hedgehog particularly influences differentiation to the medullary TEC lineage. Shh regulates cell surface MHCII expression on both cortical and medullary TEC.